Harun Farocki forms of intelligence - Alter, Nora M. 1962- (Columbia University Press, 2024)
"At the time of his death in 2014, Harun Farocki was one of the most celebrated global contemporary experimental filmmakers. His films were and are exhibited throughout the world including a major retrospective of his work at MoMA in 2011. However, his status as an "art star" came relatively late. For much of his career, he worked in the margins of the culture industry, making independent films and commissions for television. Taken as a whole, Farocki's creative activity represents an enormous output comprising more than one hundred works of varying length, format, and media. He began by making politically engaged films in Super 8 and 16 mm, often with members of the Red Army Faction. This initial period was followed by his work for German television and independent film productions that investigated image creation and subjects of labor. Finally, in the last phase of his career, Farocki recalibrated his film practice to create art installations, working in digital and multi-channel formats, and finding a global audience. What remained constant in Farocki's work was a rigorous investigation of images, their political possibilities, and how they are often manipulated by those in power. He sought to understand how the media world he lived in functioned and viewed his films as a critique and serving a pedagogical function addressing a range of viewers. Farocki's career is also a lens to understand avant-garde and experimental filmmaking over the past half a century as materials shift from celluloid to video, and finally digital; as exhibition platforms migrate from theatres to televisions, to galleries, and finally the internet"--
Keywords: Farocki, Harun -- 1944-2014; Film; Farocki, Harun / Criticism and interpretation; Independent filmmakers / Germany / Biography; Cinéastes indépendants / Allemagne / Biographies